2020
DOI: 10.3390/cancers12092663
|View full text |Cite
|
Sign up to set email alerts
|

Combining Correlated Outcomes and Surrogate Endpoints in a Network Meta-Analysis of Colorectal Cancer Treatments

Abstract: This study aimed to investigate the efficacy and safety of systemic therapies in the treatment of unresectable advanced or metastatic colorectal cancer. Predicted hazard ratios (HRs) and their 95% credible intervals (CrIs) for overall survival (OS) were calculated from the odds ratio (OR) for the overall response rate and/or HR for progression-free survival using multivariate random effects (MVRE) models. We performed a network meta-analysis (NMA) of 49 articles to compare the efficacy and safety of FOLFOX/FOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…We also used the trace plot and density plot to assess convergence. Surface under the cumulative ranking curve (SUCRA) is a representative number of the overall ranking, and a lower SUCRA value denotes a lower probability ( Daly et al, 2019 ; Hoang and Kim, 2020 ). We ranked interventions by calculating the values of SUCRA.…”
Section: Methodsmentioning
confidence: 99%
“…We also used the trace plot and density plot to assess convergence. Surface under the cumulative ranking curve (SUCRA) is a representative number of the overall ranking, and a lower SUCRA value denotes a lower probability ( Daly et al, 2019 ; Hoang and Kim, 2020 ). We ranked interventions by calculating the values of SUCRA.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the network meta-analysis [11] there were no differences in adverse events observed among patients with mCRC receiving cetuximab-FOLFIRI and panitumumab-FOLFOX as first-line treatment. Furthermore, the ASPECCT trial with the head-to-head comparison of cetuximab and panitumumab concluded that the adverse events of any grade were similar except for infusion reaction, skin toxicity, and hypomagnesaemia [32].…”
Section: Adverse Eventsmentioning
confidence: 99%
“…The results showed that cetuximab and panitumumab had similar efficacy and incidence of adverse events; infusion reactions were a key differentiator [10]. Although there is no head-to-head comparison in the first line setting, a recently published network meta-analysis reported no significant difference in either efficacy A c c e p t e d M a n u s c r i p t (hazard ratio 1.01; 95% confidence interval 0.76-1.32) or safety of first-line cetuximab-FOLFIRI compared with panitumumab-FOLFOX [11]. With comparable efficacy and safety, cost may be an important differentiating factor between these treatments.…”
Section: Introductionmentioning
confidence: 99%